Microcrystal wear-resistant alumina ceramic and preparation method thereof
By using raw materials such as fused corundum powder and alumina samide, and adding additives such as diopside and calcium fluorosilicate, the problem of poor wear resistance of alumina ceramics is solved, and the efficient wear resistance of the ceramics is improved and the sintering temperature is reduced.
Patent Information
- Application Number
- CN202411955701.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-28
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-28
AI Technical Summary
The poor wear resistance of alumina ceramic materials limits its promotion in practical applications.
Electromel corundum powder and aluminite are used as the main raw materials, and by adding diopylene, calcium fluorosilicate, neodymium trioxide, nickel aluminate and strontium oxide and other additives and wear resistance aids, the microstructure of alumina ceramics is improved, the sintering temperature is reduced, and the density and wear resistance are improved.
The wear resistance of alumina ceramics is significantly improved, the sintering temperature is reduced, the denseness and fracture toughness of the ceramics are improved, so that it can show excellent wear resistance under high temperature and high pressure conditions.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of alumina ceramic preparation, and specifically relates to a microcrystalline wear-resistant alumina ceramic and a preparation method thereof. Background Art
[0002] Microcrystalline alumina ceramics refer to high-purity α-Al 2 O 3 Alumina ceramic materials with a crystal phase grain size of less than 6μm and corundum as the main crystal phase are made of aluminum oxide powder as the main raw material through various ceramic processes. They have high melting point, high hardness, good mechanical properties, corrosion resistance, insulation and other excellent properties. Corundum is an extremely hard material in nature with a Mohs hardness of 9, second only to diamond. The strength of corundum ceramics is very high, with a melting point of 2050℃, and this high strength can still be maintained at high temperatures above 1000℃. It can also be used for a long time under high temperature and oxygen-rich conditions, which is far superior to ordinary steel and alloy steel. Corundum has very good thermal conductivity, with a thermal conductivity of 29 W / m·K at room temperature, which is only slightly lower than the thermal conductivity of steel, and the dielectric loss at high frequencies is less than 10 -4 , is one of the best high-frequency insulation materials.
[0003] Microcrystalline alumina ceramics can generally be divided into two types: high-purity type and ordinary type. High-purity microcrystalline alumina ceramics refer to Al 2 O 3 Alumina ceramic materials with an alumina content of more than 99.9% have a sintering temperature of up to 1650-1990°C and a transmission wavelength in the range of 1-6μm. They are often used as high-pressure sodium lamp tubes due to their light transmittance and resistance to alkali metal corrosion.
[0004] Ordinary microcrystalline alumina ceramics 2 O 3 Different content can be divided into 99, 95, 92, 90, 85 porcelain and other varieties (sometimes Al 2 O 3 Those with a content of 80% or 75% are also classified as ordinary alumina ceramics. Among them, 99 alumina ceramic materials are often used to make high-temperature crucibles, refractory furnace tubes and other special wear-resistant materials (such as ceramic bearings, ceramic seals and water valve plates). In the electronics industry, they can be used as integrated circuit substrates and high-frequency insulation materials. In the chemical industry, they are often used as catalyst carriers, etc.; 95, 92, and 90 alumina ceramics are mainly used as corrosion-resistant, wear-resistant materials and wear-resistant parts; 85 ceramics are often mixed with some talc to improve electrical properties and mechanical strength. They can be sealed with metals such as niobium and tantalum and used as electric vacuum devices.
[0005] However, the chemical bond of alumina ceramic material is an ionic bond, which has strong directionality and high binding energy, resulting in high brittleness, strong crack sensitivity and poor wear resistance. The wear resistance of alumina ceramic material greatly limits the promotion and application of this material. Therefore, how to effectively improve the wear resistance of alumina ceramic is the core issue in the research field of alumina ceramic materials. Summary of the invention
[0006] The purpose of the present invention is to provide a microcrystalline wear-resistant alumina ceramic having excellent wear resistance and a preparation method thereof.
[0007] The microcrystalline wear-resistant alumina ceramic of the present invention is composed of the following raw materials, measured by weight: 80-83 parts of fused corundum powder, 17-20 parts of gibbsite, 0.4-0.6 parts of diopside, 1.3-1.5 parts of calcium fluorosilicate, 0.1-0.13 parts of neodymium trioxide, 1.2-1.4 parts of nickel aluminate, 0.1-0.15 parts of strontium oxide, and 5-6 parts of sodium tripolyphosphate.
[0008] in: The particle size of fused corundum powder is 14-20μm.
[0009] The microcrystalline wear-resistant alumina ceramic of the present invention is mainly composed of fused corundum powder and gibbsite. The fused corundum itself has extremely high hardness and wear resistance. The gibbsite is compounded with a part of gibbsite to fundamentally ensure the wear resistance of the prepared alumina ceramic. The gibbsite is thermally decomposed to form boehmite, which is converted into different alumina transition phases and finally converted into α-Al at the firing temperature. 2 O 3Diopside and calcium fluorosilicate are used as fluxes. Diopside has solvent properties and a strong mineralizer effect. By introducing diopside, a liquid phase is generated during the high-temperature sintering process. Under the action of surface tension, the liquid phase flows into the pores, reducing the porosity of the ceramic body and increasing the density of the ceramic body, thereby reducing the sintering temperature; the addition of calcium fluorosilicate can reduce the accumulation of grains and the sintering temperature, reduce the viscosity of the glass phase, and promote the sintering of alumina ceramics at a lower temperature. Neodymium trioxide, nickel aluminate and strontium oxide are added as wear-resistant additives. The addition of neodymium trioxide can affect the microstructure of alumina ceramics, reduce the content of glass phase at grain boundaries, and effectively alleviate the stress concentration at grain boundaries caused by different thermal expansion coefficients. In addition, neodymium trioxide promotes the formation of the second phase on the grain boundary, reduces the microstress between grains and the probability of grains being pulled out, thereby improving the wear resistance of the prepared alumina ceramics; nickel aluminate has a spinel structure, Al occupies the octahedral position, and Ni occupies the tetrahedral position. It itself has excellent high temperature stability, acid and alkali resistance, and wear resistance. By adding nickel aluminate, the fracture toughness and hardness of alumina ceramics are improved, so that alumina ceramics will not be broken when subjected to impact or stress, thereby improving its wear resistance. In addition, the addition of nickel aluminate can also change the wear mechanism of alumina ceramics, transforming it from abrasive wear to adhesive wear, thereby reducing the wear rate of alumina ceramics; under high-temperature sintering, strontium oxide can form a solid solution with alumina, and through solid solution strengthening, the hardness and wear resistance of alumina ceramics are improved, and the fracture toughness of alumina ceramics is enhanced. Sodium tripolyphosphate in the raw material acts as a wetting binder.
[0010] The preparation method of the microcrystalline wear-resistant alumina ceramics of the present invention comprises the following steps: (1) Evenly mixing fused corundum powder, gibbsite, diopside, calcium fluorosilicate, neodymium trioxide, nickel aluminate, strontium oxide and sodium tripolyphosphate to obtain a mixture, and then wet-ball milling and drying to obtain a powder; (2) The powder is placed in a mold and pressed into shape, and then dried and sintered to prepare microcrystalline wear-resistant alumina ceramics.
[0011] in: The mass of water added during wet ball milling in step (1) accounts for 30-33% of the mass of the mixture and water, and the ball milling time is 40-41 hours.
[0012] In step (1), the drying temperature is 105-108°C and the drying time is 7.5-7.7h.
[0013] The pressure of the pressing molding in step (2) is 83-85 MPa.
[0014] In step (2), the drying temperature is 103-105° C. and the drying time is 4-4.2 h.
[0015] The sintering in step (2) is performed by heating the temperature to 730-750°C at a rate of 3.5°C / min, then heating the temperature to 1500-1520°C at a rate of 2.2°C / min and keeping the temperature for 3.5-3.7h, and finally cooling the furnace to room temperature.
[0016] Compared with the prior art, the present invention has the following beneficial effects: (1) The microcrystalline wear-resistant alumina ceramics described in the present invention use fused corundum powder and gibbsite as the main raw materials, which fundamentally guarantee the mechanical properties of the prepared alumina ceramics; use diopside and calcium fluorosilicate as fluxes to reduce the firing temperature of the alumina ceramics and improve the density; use neodymium trioxide, nickel aluminate and strontium oxide as wear-resistant additives, and utilize the synergistic effect between the three to improve the microstructure of the alumina ceramics, avoid stress concentration at the grain boundaries, and generate a second reinforcement phase to improve the wear resistance of the alumina ceramics. As a result, the raw materials interact with each other, ensuring that the prepared alumina ceramics have excellent wear resistance while reducing the firing temperature.
[0017] (2) The method for preparing the microcrystalline wear-resistant alumina ceramics of the present invention has a simple process, easy-to-control parameters, is suitable for mass production, and the quality of the prepared alumina ceramics is high. DETAILED DESCRIPTION
[0018] The present invention is further described below with reference to the embodiments.
[0019] Example 1 The microcrystalline wear-resistant alumina ceramic described in this embodiment 1 is composed of the following raw materials, measured in parts by weight: 82 parts of fused corundum powder, 18 parts of gibbsite, 0.5 parts of diopside, 1.4 parts of calcium fluorosilicate, 0.12 parts of neodymium trioxide, 1.3 parts of nickel aluminate, 0.13 parts of strontium oxide, and 5.5 parts of sodium tripolyphosphate.
[0020] in: The particle size of the fused corundum powder is 18 μm.
[0021] The preparation method of the microcrystalline wear-resistant alumina ceramic described in this embodiment 1 comprises the following steps: (1) Evenly mixing fused corundum powder, gibbsite, diopside, calcium fluorosilicate, neodymium trioxide, nickel aluminate, strontium oxide and sodium tripolyphosphate to obtain a mixture, and then wet-ball milling and drying to obtain a powder; (2) The powder is placed in a mold and pressed into shape, and then dried and sintered to prepare microcrystalline wear-resistant alumina ceramics.
[0022] in: The mass of water added during wet ball milling in step (1) accounts for 31% of the mass of the mixture and water, and the ball milling time is 40.5 h.
[0023] In step (1), the drying temperature is 106°C and the drying time is 7.6 hours.
[0024] The pressure of the pressing molding in step (2) is 84 MPa.
[0025] In step (2), the drying temperature is 104° C. and the drying time is 4.1 h.
[0026] The sintering in step (2) is to heat up to 740°C at a rate of 3.5°C / min, then heat up to 1510°C at a rate of 2.2°C / min and keep at that temperature for 3.6h, and finally cool to room temperature in the furnace.
[0027] The wear resistance of the microcrystalline wear-resistant alumina ceramic prepared in Example 1 is 12000 revolutions, level 5, the pollution resistance is level 5, and the fracture toughness is 6.9 MPa·m 1 / 2 Among them, GB / T 3810.7-2016 is used to test the wear resistance classification, GB / T3810.14-2016 is used to test the pollution resistance, and GB / T 23806-2009 is used to test the fracture toughness.
[0028] Example 2 The microcrystalline wear-resistant alumina ceramic described in this embodiment 2 is composed of the following raw materials, measured in parts by weight: 80 parts of fused corundum powder, 20 parts of gibbsite, 0.4 parts of diopside, 1.5 parts of calcium fluorosilicate, 0.1 parts of neodymium trioxide, 1.4 parts of nickel aluminate, 0.1 parts of strontium oxide, and 6 parts of sodium tripolyphosphate.
[0029] in: The particle size of fused corundum powder is 14 μm.
[0030] The preparation method of the microcrystalline wear-resistant alumina ceramic described in this embodiment 2 comprises the following steps: (1) Evenly mixing fused corundum powder, gibbsite, diopside, calcium fluorosilicate, neodymium trioxide, nickel aluminate, strontium oxide and sodium tripolyphosphate to obtain a mixture, and then wet-ball milling and drying to obtain a powder; (2) The powder is placed in a mold and pressed into shape, and then dried and sintered to prepare microcrystalline wear-resistant alumina ceramics.
[0031] in: The mass of water added during wet ball milling in step (1) accounts for 33% of the mass of the mixture and water, and the ball milling time is 41 hours.
[0032] In step (1), the drying temperature is 108°C and the drying time is 7.5h.
[0033] The pressure of the pressing molding in step (2) is 85 MPa.
[0034] In step (2), the drying temperature is 105°C and the drying time is 4 hours.
[0035] The sintering in step (2) is to heat up to 750°C at a rate of 3.5°C / min, then heat up to 1520°C at a rate of 2.2°C / min and keep at that temperature for 3.7h, and finally cool to room temperature in the furnace.
[0036] The wear resistance of the microcrystalline wear-resistant alumina ceramic prepared in Example 2 is 12000 revolutions, level 5, the pollution resistance is level 5, and the fracture toughness is 7.1 MPa·m 1 / 2 Among them, GB / T 3810.7-2016 is used to test the wear resistance classification, GB / T3810.14-2016 is used to test the pollution resistance, and GB / T 23806-2009 is used to test the fracture toughness.
[0037] Example 3 The microcrystalline wear-resistant alumina ceramic described in this embodiment 3 is composed of the following raw materials, measured in parts by weight: 83 parts of fused corundum powder, 17 parts of gibbsite, 0.6 parts of diopside, 1.3 parts of calcium fluorosilicate, 0.13 parts of neodymium trioxide, 1.2 parts of nickel aluminate, 0.15 parts of strontium oxide, and 5 parts of sodium tripolyphosphate.
[0038] in: The particle size of the fused corundum powder is 20 μm.
[0039] The preparation method of the microcrystalline wear-resistant alumina ceramic described in this embodiment 3 comprises the following steps: (1) Evenly mixing fused corundum powder, gibbsite, diopside, calcium fluorosilicate, neodymium trioxide, nickel aluminate, strontium oxide and sodium tripolyphosphate to obtain a mixture, and then wet-ball milling and drying to obtain a powder; (2) The powder is placed in a mold and pressed into shape, and then dried and sintered to prepare microcrystalline wear-resistant alumina ceramics.
[0040] in: The mass of water added during wet ball milling in step (1) accounts for 30% of the mass of the mixture and water, and the ball milling time is 40 hours.
[0041] In step (1), the drying temperature is 105°C and the drying time is 7.7h.
[0042] The pressure of the pressing molding in step (2) is 83 MPa.
[0043] In step (2), the drying temperature is 103° C. and the drying time is 4.2 h.
[0044] The sintering in step (2) is to heat the mixture to 730°C at a rate of 3.5°C / min, then heat the mixture to 1500°C at a rate of 2.2°C / min and keep the temperature for 3.5h, and finally cool the mixture to room temperature.
[0045] The wear resistance of the microcrystalline wear-resistant alumina ceramic prepared in Example 3 is 12000 revolutions, level 5, the pollution resistance is level 5, and the fracture toughness is 6.8 MPa·m 1 / 2 Among them, GB / T 3810.7-2016 is used to test the wear resistance classification, GB / T3810.14-2016 is used to test the pollution resistance, and GB / T 23806-2009 is used to test the fracture toughness.
[0046] Comparative Example 1 The preparation method of the microcrystalline wear-resistant alumina ceramic described in this comparative example 1 is the same as that of Example 1, and the only difference is that the raw material composition is different. The microcrystalline wear-resistant alumina ceramic described in this comparative example 1 is composed of the following raw materials in parts by weight: 82 parts of fused corundum powder, 18 parts of gibbsite, 0.5 parts of diopside, 1.4 parts of calcium fluorosilicate, 1.3 parts of nickel aluminate, 0.13 parts of strontium oxide, and 5.5 parts of sodium tripolyphosphate.
[0047] The wear resistance of the microcrystalline wear-resistant alumina ceramic prepared in Comparative Example 1 is 12000 revolutions, level 4, the pollution resistance is level 4, and the fracture toughness is 5.1 MPa·m 1 / 2 Among them, GB / T 3810.7-2016 is used to test the wear resistance classification, GB / T3810.14-2016 is used to test the pollution resistance, and GB / T 23806-2009 is used to test the fracture toughness.
[0048] Comparative Example 2 The preparation method of the microcrystalline wear-resistant alumina ceramic described in this comparative example 2 is the same as that of Example 1, and the only difference is that the raw material composition is different. The microcrystalline wear-resistant alumina ceramic described in this comparative example 2 is composed of the following raw materials in parts by weight: 82 parts of fused corundum powder, 18 parts of gibbsite, 0.5 parts of diopside, 1.4 parts of calcium fluorosilicate, 0.12 parts of neodymium trioxide, 0.13 parts of strontium oxide, and 5.5 parts of sodium tripolyphosphate.
[0049] The wear resistance of the microcrystalline wear-resistant alumina ceramic prepared in Comparative Example 2 is 12000 revolutions, level 3, the pollution resistance is level 4, and the fracture toughness is 4.4 MPa·m 1 / 2 Among them, GB / T 3810.7-2016 is used to test the wear resistance classification, GB / T3810.14-2016 is used to test the pollution resistance, and GB / T 23806-2009 is used to test the fracture toughness.
[0050] Comparative Example 3 The preparation method of the microcrystalline wear-resistant alumina ceramic described in this comparative example 3 is the same as that of Example 1, and the only difference is that the raw material composition is different. The microcrystalline wear-resistant alumina ceramic described in this comparative example 3 is composed of the following raw materials in parts by weight: 82 parts of fused corundum powder, 18 parts of gibbsite, 0.5 parts of diopside, 1.4 parts of calcium fluorosilicate, 0.12 parts of neodymium trioxide, 1.3 parts of nickel aluminate, and 5.5 parts of sodium tripolyphosphate.
[0051] The wear resistance of the microcrystalline wear-resistant alumina ceramic prepared in Comparative Example 3 is 12,000 revolutions, level 4, the pollution resistance is level 4, and the fracture toughness is 5.5 MPa·m 1 / 2 Among them, GB / T 3810.7-2016 is used to test the wear resistance classification, GB / T3810.14-2016 is used to test the pollution resistance, and GB / T 23806-2009 is used to test the fracture toughness.
Claims
1. A microcrystalline wear-resistant alumina ceramic, characterized in that: The invention is composed of the following raw materials in parts by weight: 80-83 parts of fused corundum powder, 17-20 parts of gibbsite, 0.4-0.6 parts of diopside, 1.3-1.5 parts of calcium fluorosilicate, 0.1-0.13 parts of neodymium trioxide, 1.2-1.4 parts of nickel aluminate, 0.1-0.15 parts of strontium oxide and 5-6 parts of sodium tripolyphosphate.
2. The microcrystalline wear-resistant alumina ceramic according to claim 1, characterized in that: The particle size of fused corundum powder is 14-20μm.
3. A method for preparing the microcrystalline wear-resistant alumina ceramic according to claim 1, characterized in that: It consists of the following steps: (1) Evenly mixing fused corundum powder, gibbsite, diopside, calcium fluorosilicate, neodymium trioxide, nickel aluminate, strontium oxide and sodium tripolyphosphate to obtain a mixture, and then wet-ball milling and drying to obtain a powder; (2) The powder is placed in a mold and pressed into shape, and then dried and sintered to prepare microcrystalline wear-resistant alumina ceramics.
4. The method for preparing microcrystalline wear-resistant alumina ceramics according to claim 3, characterized in that: The mass of water added during wet ball milling in step (1) accounts for 30-33% of the mass of the mixture and water, and the ball milling time is 40-41 hours.
5. The method for preparing microcrystalline wear-resistant alumina ceramics according to claim 3, characterized in that: In step (1), the drying temperature is 105-108°C and the drying time is 7.5-7.7h.
6. The method for preparing microcrystalline wear-resistant alumina ceramics according to claim 3, characterized in that: The pressure of the pressing molding in step (2) is 83-85 MPa.
7. The method for preparing microcrystalline wear-resistant alumina ceramics according to claim 3, characterized in that: In step (2), the drying temperature is 103-105°C and the drying time is 4-4.2h.
8. The method for preparing microcrystalline wear-resistant alumina ceramics according to claim 3, characterized in that: The sintering in step (2) is performed by heating the temperature to 730-750°C at a rate of 3.5°C / min, then heating the temperature to 1500-1520°C at a rate of 2.2°C / min and keeping the temperature for 3.5-3.7h, and finally cooling the furnace to room temperature.
Citation Information
Patent Citations
stuff
AT15389S
Microcrystalline alumina wear resistant ceramics and preparation method thereof
CN102432317A
Preparation method of abrasion-proof aluminum oxide ceramics
CN103626479A
Rare-earth alumina ceramic composite material and preparation method thereof
CN108083779A
Microcrystalline wear-resistant ceramic grinding body as well as preparation method and application thereof
CN108793976A
Cited By
Physical ceramic corundum grinding material and preparation method thereof
CN122212692A